Assessment of patient experiences following total sacrectomy for primary malignant sacral tumors: A qualitative study. Issue 8 (8th November 2019) - Wang, Yifei; Liang, Weiming; Qu, Shan; Zhang, Yidan; Du, Zhiye; Ji, Tao; Qu, Huayi; Gorlick, Richard; Guo, Wei
Abstract: Background and Objectives: Few reports have investigated patient experiences following total en bloc sacrectomy. The aims of this study were to obtain a deeper understanding of patients' personal experiences, needs, and satisfaction with the treatment to reveal areas in which perioperative and long‐term patient care can be improved. Methods: A qualitative design was applied to examine patient experiences and supportive care needs. Patients treated between 2007 and 2017 were identified from our institutional database. Results: A total of 28 survivors were interviewed (13 females, age 13‐75 years). Eight themes were identified: the effect of surgery on patients' (a) daily lives, (b) social activities, (c) work or school activities, (d) and family lives; (e) acceptance of ostomy surgery; (f) need for guidance regarding long‐term rehabilitation; (g) satisfaction with the medical services provided in the hospital; and (h) satisfaction with the treatment outcomes. Conclusion: Total en bloc sacrectomy can yield satisfactory oncological outcomes; however, the procedure is a life‐changing event for patients and their families. Physicians must provide long‐term support and guidance after surgery to enable patients to fully understand and cope with the changes in their lives.